2009
DOI: 10.1105/tpc.108.064857
|View full text |Cite
|
Sign up to set email alerts
|

The ABC Transporter PXA1 and Peroxisomal β-Oxidation Are Vital for Metabolism in Mature Leaves ofArabidopsisduring Extended Darkness    

Abstract: Fatty acid b-oxidation is essential for seedling establishment of oilseed plants, but little is known about its role in leaf metabolism of adult plants. Arabidopsis thaliana plants with loss-of-function mutations in the peroxisomal ABC-transporter1 (PXA1) or the core b-oxidation enzyme keto-acyl-thiolase 2 (KAT2) have impaired peroxisomal b-oxidation. pxa1 and kat2 plants developed severe leaf necrosis, bleached rapidly when returned to light, and died after extended dark treatment, whereas the wild type was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
147
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(160 citation statements)
references
References 67 publications
8
147
1
2
Order By: Relevance
“…CGI58 is one candidate, since the protein has lipase activity (Ghosh et al, 2009) and the mutant accumulates TAG in its leaves to around 0.2% of dry weight (James et al, 2010), which is higher than we detected in sdp1. The disruption of fatty acid b-oxidation also leads to TAG accumulation in leaves (Slocombe et al, 2009;James et al, 2010), but the impact on total fatty acid content appears to be small (Yang and Ohlrogge, 2009), unless the tissue is subjected to carbohydrate starvation (Kunz et al, 2009;Slocombe et al, 2009). Therefore, TAG turnover in the cytosol may simply be less rapid in leaves than in roots and stems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CGI58 is one candidate, since the protein has lipase activity (Ghosh et al, 2009) and the mutant accumulates TAG in its leaves to around 0.2% of dry weight (James et al, 2010), which is higher than we detected in sdp1. The disruption of fatty acid b-oxidation also leads to TAG accumulation in leaves (Slocombe et al, 2009;James et al, 2010), but the impact on total fatty acid content appears to be small (Yang and Ohlrogge, 2009), unless the tissue is subjected to carbohydrate starvation (Kunz et al, 2009;Slocombe et al, 2009). Therefore, TAG turnover in the cytosol may simply be less rapid in leaves than in roots and stems.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the disruption of several other genes associated with lipid catabolism can also lead to TAG accumulation in vegetative tissues, although heterotrophic tissues have not generally been investigated (Kunz et al, 2009;Slocombe et al, 2009;James et al, 2010). PXA1 is a peroxisomal ATPbinding cassette transporter that is required for fatty acid import for b-oxidation (Zolman et al, 2001), and CGI58 is an enzyme that has been reported to have lipase, phospholipase, and lysophosphatidic acid acyltransferase activities (Ghosh et al, 2009).…”
Section: Tag Accumulation In Sdp1 Roots Is Greater Than In Several Otmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we suggest that there is also a homeostasis between TAG biosynthesis and degradation in higher plants. Experimental evidence has indicated that extended darkness treatment of fatty acid breakdown mutants, such as pxa1, cts2, and acx1acx2, led to the ectopic accumulation of TAG in the leaf (Kunz et al, 2009;Slocombe et al, 2009). The TAG content in naturally senescing leaves of fatty acid breakdown mutants was also increased (Slocombe et al, 2009).…”
Section: There Is a Homeostasis Between Tag Biosynthesis And Degradatmentioning
confidence: 99%
“…The transcripts encoding thiolase and ACX4 accumulate during carbon-starvation (Charlton et al, 2005;Contento and Bassham, 2010), implying that fatty acid b-oxidation increases upon nutrient deprivation. Indeed, several b-oxidation mutants, including pxa1 and mutants with reduced thiolase activity, die prematurely in extended darkness (Dong et al, 2009;Kunz et al, 2009). Both pxa1 and sdp1 mutants catabolize triacylglycerol inefficiently in extended darkness, but sdp1 lowers free fatty acid accumulation and ameliorates plant death in dark-treated pxa1 mutants (Fan et al, 2017), implying that free fatty acid toxicity rather than carbon starvation contributes to pxa1 death.…”
mentioning
confidence: 99%